A case study on effect of grouping technique in a multi-stage hybrid flow shop. (2016) - Pugazhenthi, R.; Xavior, M. Anthony; Saravanan, R.
In general, the hybrid flow shop problem (HFSP) is complex in nature. This papers deals with the effect of grouping technique in a multi-stage HFSP with practical relevance. With respect to increase in stages of HSFP, the level of complexity in solving the problem is increased. This paper deals with the problem which is motivated by practical need for operational scheduling in automobile spares manufacturing industry. The venture of this attempt is throughput related, i.e., minimising makespan. The simulation algorithms were used to find answers of many 'what if?' questions. The parameters included in this problem are queue length, mean lead time, machine utilisation to optimise the manufacturing strategy. In this problem, queue discipline was considered by applying first-in-first-out (FIFO) at all stages. The proposed group schedule yielded minimum makespan, acceptable queue length and significantly improved machine utilisation in the real-time examination.